A complete depolymerization of scrap tire with supercritical water participation: A molecular dynamic simulation study. (15th June 2019) - Yan, Shuo; Xia, Dehong; Zhang, Xinru; Jiang, Binfan
Graphical abstract: Highlights: Depolymerization of scrap tire (ST) with supercritical water (SCW) was simulated. The depolymerization process and reaction pathway of ST with SCW was revealed. H3 O and OH radicals released by SCW could facilitate further depolymerization. More than 95% of organic components in ST depolymerized with SCW participation. Temperature can dominate the component of final products from ST. Abstract: The growth of scrap tire (ST) has become an urgent environmental problem. In this work, the depolymerization process of ST in supercritical water (SCW) was studied with the ReaxFF molecular dynamic simulation. The depolymerization process and reaction pathway of ST in SCW were revealed. The simulation results indicated that the SCW molecules could promote the depolymerization of rubber into smaller molecules by releasing the OH radicals. After providing the OH radicals, the SCW molecules banded with the free H and turned into H3 O radicals which were the main resources to produce H2 . In the ST-SCW reaction system, more than 95% organic components in ST depolymerized into the valuable fuel (oil and fuel gas). The main compound in oil product was light oil with low viscosity. The gas products included the H2, CO and C1-C4 gas. It was found that reaction temperature could dominate the component of final products from ST. In order to produce more oil, the optimal temperature to recycle ST with SCW participation was 647–659 K. This study demonstrates the feasibility of SCW in recovering the chemical products from ST, and provides a theoretical support for its further development.